2005
DOI: 10.2337/diacare.28.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dual Blockade With Candesartan and Lisinopril in Hypertensive Patients With Diabetes

Abstract: OBJECTIVE -To assess and compare the long-term effects of the combination of candesartan and lisinopril with high-dose lisinopril on systolic blood pressure in patients with hypertension and diabetes.RESEARCH DESIGN AND METHODS -This was a prospective, randomized, parallel-group, double-blind, double-dummy study with a 12-month follow-up. Drug therapy was either lisinopril 40 mg once daily or dual-blockade treatment with candesartan 16 mg once daily and lisinopril 20 mg once daily. The study comprised 75 type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 27 publications
2
56
2
4
Order By: Relevance
“…In the design of these studies, an ARB was added to the maximum dose of an ACEI, or high doses of an ACEI and an ARB were combined without dose adjustment. On the other hand, the Candesartan and Lisinopril Microalbuminuria (CALM) II study showed that 40 mg/day of lisinopril and the combination of 20 mg lisinopril and 16 mg candesartan caused similar reductions in both BP and ACR (9). In contrast, Fujisawa et al reported that in patients with diabetic nephropathy who had been treated with an ACEI or ARB, halving the dose of the RAS inhibitor and combining it with a half dose of an other RAS inhibitor resulted in a significant reduction in ACR as compared with the value before combination (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the design of these studies, an ARB was added to the maximum dose of an ACEI, or high doses of an ACEI and an ARB were combined without dose adjustment. On the other hand, the Candesartan and Lisinopril Microalbuminuria (CALM) II study showed that 40 mg/day of lisinopril and the combination of 20 mg lisinopril and 16 mg candesartan caused similar reductions in both BP and ACR (9). In contrast, Fujisawa et al reported that in patients with diabetic nephropathy who had been treated with an ACEI or ARB, halving the dose of the RAS inhibitor and combining it with a half dose of an other RAS inhibitor resulted in a significant reduction in ACR as compared with the value before combination (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that very high doses of ARB exert better antialbuminuric effects than the more commonly used doses (7). Moreover, recent studies indicate that dual blockade of the RAS with an ACEI and an ARB is superior to either drug alone in reducing proteinuria in diabetic patients (8)(9)(10)(11). However, only a few studies have examined which of the two dosing regimens-monotherapy featuring dose increments or combination therapy-is more effective (12).…”
Section: Introductionmentioning
confidence: 99%
“…34,40,[46][47][48][56][57][58][59] Clinical trials, grouped by the degree of albuminuria, demonstrating the beneficial effects of RAAS inhibition on renal end points in patients with diabetes mellitus are summarized in Table 2. 34,40,42,48,49,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Normoalbuminuria The Bergamo Nephrologic Diabetes Complications Trial (BENEDICT) is the only primary prevention study to date to demonstrate that the development of microalbuminuria can be prevented by the use of an ACE inhibitor alone or in combination with a CCB in hypertensive normoalbuminuric patients with type II diabetes. 59 …”
Section: Clinical Evidence Of Benefits Of Raas Inhibition In Patientsmentioning
confidence: 99%
“…65 In the 12-month Candesartan and Lisinopril Microalbuminuria (CALM) II trial, however, no significant differences in systolic BP or albumin:creatinine ratio were seen when combination therapy of ACE inhibitor and ARB was compared with higher doses of the ACE inhibitor. 66 Another recent study followed 28 subjects with type I diabetes who had a BP p140/80 mm Hg with residual albuminuria (albumin:creatinine ratio 410 mg/mmol) while receiving the maximal recommended renal dose of lisinopril. 69 Candesartan or amlodipine was added to lisinopril for 24 weeks.…”
Section: Multifaceted Approachesmentioning
confidence: 99%
“…30 In patients having hypertension with diabetes, there was no significant difference in SBP reduction found between lisinopril 40 mg once daily and lisinopril 20 mg in combination with candesartan 16 mg once daily. 31 In this study, significant difference in SBP reduction between ramipril+telmisartan combination and ramipril alone was seen during 4 to 12 weeks. No significant difference in the SBP reduction between two groups was seen at the end of the study.…”
Section: Discussionmentioning
confidence: 87%